Glosa do uchwały Sądu Najwyższego z 13.07.2011 r., III CZP 39/11. „Z chwilą uprawomocnienia się wyroku orzekającego rozwód obowiązek małżonków przyczyniania się do zaspokajania potrzeb rodziny (art. 27 k.r.o.) wygasa”. - Ogrodnik-Kalita, Agnieszka (Przegląd Prawno-Ekonomiczny, 2012)
Streszczenie dostępne wyłącznie w języku angielskim: The subject of the gloss is Supreme Court’s resolution of 13 July 2011 r. (III CZP 39/11). That resolulion focuses on the problem of spounse’s obligation satysfing their family material needs after divorce. According to the resolution that obligation expires at the moment of validing divorce sentence. According to the Author the Supreme Court’s opinion is correct.